Financial Sector Assessment Program : Nigeria - Banking Cross-Border Issues - International Monetary Fund; World Bank (World Bank, Washington, DC, 2013)
The introduction of new much higher minimum capital requirements and the subsequent banking sector consolidation created a platform for Nigerian banks to expand within the region and more globally. After capitalization, several Nigerian banks found themselves with large amounts of capital while there was an environment of uncertainty about the situation in Nigeria in the aftermath of the 2009 Nigerian banking crisis. This together with new market expansion opportunities gave an impulse to a number of Nigerian banks to quickly expand within West and Central Africa, as well as more globally. The global crisis itself provided Nigerian banks with opportunities to expand within Sub-Saharan Africa (SSA). With Nigerian banks' presence in many countries in the region and more globally, the Central Bank of Nigeria (CBN) needed to overhaul its traditional supervisory practices and embark on rigorous supervision of its banks on a consolidated basis taking into account all their subsidiaries and branches abroad-a task with which even advanced supervisors still struggle. This note focuses on issues of cross-border coordination and provides policy recommendations that could be taken into consideration by the CBN. Section two provides a brief description of the expansion and cross-border liquidity flows of some Nigerian banks. Section three focuses on issues related to supervisory cross-border coordination. Section four offers some recommendations. Several Nigerian banks have expanded abroad, primarily within West and Central Africa over the recent years. Banks in Nigeria with international activities have to maintain a Capital Adequacy Ratio (CAR) of at least 15 percent, compared with the CAR requirement of 10 percent for the other Nigerian banks. At least two of those banks with headquarters in Nigeria have subsidiaries across Africa and representative offices and/or subsidiaries in Europe. One regional bank has headquarters in Togo, while its main subsidiary with about 44 percent of the total assets domiciles in Nigeria. Cross-border liquidity flows of Nigerian banks fluctuated from month to month in 2012, as Nigerian banks have been becoming more active in the region. According to the CBN, initial experiences have been encouraging, but it faces some serious challenges in further strengthening of cross-border supervision. A recent CBN circular issued in May 2012, restricting Nigerian banks' capacity to capitalize their foreign subsidiaries, will seem to be an unnecessary restriction on an activity that will generally be managed through the supervisory process.